1997
DOI: 10.2747/0272-3638.18.6.497
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Ethnic Real Estate Agents in the Residential Relocation Process: A Case Study of Portuguese Homebuyers in Suburban Toronto

Abstract: This paper examines the search behavior of a sample of Portuguese and Canadianborn homebuyers in suburban Toronto, Canada. Attention is focused on the extent to which Portuguese homebuyers rely upon real estate agents from the same ethnic background and how this source can influence the homebuyer's housing search and ultimate choice of a residence. Data were obtained from a questionnaire survey that was administered to a sample of 110 Portuguese and 90 Canadian-born recent homebuyers in the city of Mississauga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
45
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 28 publications
1
45
0
Order By: Relevance
“…For example, Chan and Cheung (1985), in their study of Chinese businesses in Toronto, found that Chinese business owners benefited from certain collective resources of the community such as group solidarity, ethnic customers, and ethnic labour, although individual resources were also important. In the Portuguese community in Toronto, several studies found that community resources such as local networks and ties largely contributed to the formation, maintenance, and success of Portuguese-owned real estate businesses (Teixeira, 1998;Teixeira A Murdie, 1997). Marger and Hoffman (1992) studied ethnic businesses in Ontario and found that the success of the Hong Kong entrepreneurs was aided by the rapid growth of the Chinese population and the corresponding consumer market, and by adopting a business strategy to target labourintensive businesses that made use of a network of ethnic institutions.…”
Section: Ethnic Enclave Economymentioning
confidence: 99%
“…For example, Chan and Cheung (1985), in their study of Chinese businesses in Toronto, found that Chinese business owners benefited from certain collective resources of the community such as group solidarity, ethnic customers, and ethnic labour, although individual resources were also important. In the Portuguese community in Toronto, several studies found that community resources such as local networks and ties largely contributed to the formation, maintenance, and success of Portuguese-owned real estate businesses (Teixeira, 1998;Teixeira A Murdie, 1997). Marger and Hoffman (1992) studied ethnic businesses in Ontario and found that the success of the Hong Kong entrepreneurs was aided by the rapid growth of the Chinese population and the corresponding consumer market, and by adopting a business strategy to target labourintensive businesses that made use of a network of ethnic institutions.…”
Section: Ethnic Enclave Economymentioning
confidence: 99%
“…This ambivalent phenomenon illustrates the weakening Portuguese ties to Little Portugal. In addition, as Teixeira and Murdie (1997) As mentioned, the Portuguese in Toronto now occupy three residential domains: Little Portugal (their declining traditional core), the northern corridor, and the western suburbs, the latter two of which have been expanding since the 1980s.…”
mentioning
confidence: 93%
“…Since the 1990s, studies of the Portuguese in Toronto have increased, thanks to Teixeira and his colleagues (Teixeira 1993(Teixeira , 1998(Teixeira , 2006a(Teixeira , 2006b(Teixeira , 2007(Teixeira , 2009Teixeira and Murdie 1997;Teixeira et al 2007;Teixeira and Da Rosa 2009;Murdie and Teixeira 2011). However, there is no scholarly reference to the overall spatial structure of the Portuguese community, and the transformation process of Little Portugal has yet to be examined in detail.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, poverty and immigration are two distinct phenomena with a slight overlap Smith 1997, 2000). Moreover, some studies note that the spatial concentration of certain immigrants and minority group members may lead to the creation of a collective resource, designated by the term "ethnic capital", which strengthens the capacity for certain immigrants or minority group members to access homeownership by fostering their institutional organization or their control over specific segments of the housing market (Breton 1964;Haan 2005;Leloup 2007;Teixeira and Murdie 1997). In brief, spatial concentration or other dimensions of residential segregation cannot be systematically associated with poor housing conditions and urban deprivation.…”
Section: Theoretical Backgroundmentioning
confidence: 99%